Risco versus retorno a partir de dados contábeis de empresas brasileiras: uma contribuição empírica - Silveira, José Augusto Giesbrecht da (1990)
The nuclear part of this doctoral dissertation is a research work, which investigates the trade-off between accounting risk and return in 10 Brazilian economic sectors. For the 1978-87 period, in a sample of 344 firms, a negative risk/return association was detected in eight sectors and a positive or neutral one in only two sectors. Pooling together data for the 344 firms, a negative relationship between risk and return was found. After splitting the sample according to firm profitability, an essentially negative risk/return association was identified in the less profitable half of the firms studied, both within and across sectors. On the other hand, the more profitable firms in the sample exhibited a lack of significant association between accounting risk and return, within and across sectors.